Shin-gi-tai as a guiding principle in Kodokan judo. Yet, another example of historical reinvention? (Revista de Artes Marciales Asiáticas, 2025)
Judo national governing bodies in recent years through slogans, posters, cartoons, and web site information have attempted to reignite their members’ appreciation for a judo morality constructed on Japanese bushido. Similarly, several judo federations actively promote ‘shin-gi-tai’ (mind-technique-body) as a guiding principle for rank promotions and conduct allegedly in association with Kano Jigoro’s philosophy. Using translation, critical and heuristic analysis of relevant original historical Japanese sources, it is the purpose of this paper to investigate the origin, etymology and justification of shin-gi-tai as a pre-existing principle in Kodokan judo. Our results show that shin-gi-tai was first used in judo by Michigami Haku while teaching in Shanghai in the 1940s. After his arrival in France in 1953, the concept was introduced and distributed within the Western judo world. However, Michigami was not the original author. It was on the island of Kyushu, from where Michigami hailed, that the term shin-gi-tai appears to have been first used in the Heiho shingitai oboegaki (Memorandum on military arts and mind-technique-body), a text authored by Toyoda Masanaga, an 18th century Niten ichi-ryu heiho swordsman influenced by Miyamoto Musashi. A similar term, shinkitai, later entered sumo through the Yoshida family, also active in Kyushu, who became responsible for the administration of sumo in the late Meiji period. Michigami as a young man had practiced both kendo and sumo. There is no link between Kano Jigoro and shin-gi-tai. While it is acceptable to use shin-gi-tai or any other legitimate meme in coaching athletes, asserting that it represents a fundamental principle that guides rank promotions and ethics in judo is nothing but historical reinvention that lacks any basis.